Persistence preferred – on future residential (im)mobility among the generation 50plus - Kramer, Caroline; Pfaffenbach, Carmella (ERDKUNDE, 2009)
The current academic discussion on residential mobility among the elderly mainly deals with two contradictory processes: Either it is assumed that future generations will behave as this generation does with respect to their conceptions of life and their choice of residence and a significant number will leave the cities upon retirement in order to settle in suburbia. Or a fundamental trend reversal is expected towards reurbanization and urban revival for all age groups and thus the generation 50plus also. For an investigation in the Munich metropolitan area, whose results are discussed here, it was at first assumed that the seniors of the generation 50plus would clearly behave differently than today’s elderly, i.e. would be characterized by different lifestyles that would perhaps also be realized in other (residential) locations. The evaluation of the empirical data showed that those surveyed in the Munich metropolitan area are neither planning to leave the city in large numbers nor are large numbers of former suburbanites planning on moving to the cities. Thus, after retirement, persistence with respect to staying in their principal residences combined with temporary stays in their second residence arrangements – if available – is planned. The city of Munich will most likely not experience a renaissance among the generation 50plus, since there was no “crisis of the city”. Indeed, Munich remains an attractive location for those surveyed – as long as they can afford to live in the city. The main challenges for urban housing market policies will be to provide “affordable” housing in the city.